What do we know about the Oldest Manuscript of the Tatars of the Grand Duchy of Lithuania? (¸e Kitab of 1631 – Transliteration, Orthography, Translation, Comments) - Kulwicka - Kamińska, Joanna; Łapicz, Czesław (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English]The Kitab of 1631 is an object of understandable interest for researchers, because this manuscript must have been one of the first links in the chain of manuscript copies of religious books of the Tatars of the Grand Duchy of Lithuania (GDL). Unfortunately, soon after the manuscript was discovered, it disappeared along with the microfilm which was made by its first researchers. There are faint traces of the comprehensive monument (342 sheets) in the form of a brief description (the so-called imprint) in an unpublished manuscript and a reproduction of a sample page in an article of one of those who discovered the manuscript – Maciej Konopacki. Last year in autumn, the perusal of a collection of Tatariana from the collections of the Historical Museum of Białystok brought to light four frames of photographic film that present four heretofore unknown pages of the Kitab of 1631. This furnishes an opportunity to enhance our knowledge about this valuable monument. This article includes a copy of one of the manuscript pages along with its transliteration in a strictly scholarly version as well as a translation from Old Belarusian into Polish. The text is accompanied by a historical and philological commentary.
Keywords: kitab studies, Tatariana of the Grand Duchy of Lithuania, transliteration and transcription of kitabs